Legal Certainty of the Implementation of Mass Itsbat Nikah in Minimizing Marriages Without Certifitaces in the Religious Court of Sukabumi City - Nadia Agustina; Prahasti Suyaman; Temmy Fitriah Alfiany (Yayasan Adra Karima Hubbi, 2023)
Background. The Tax Court, basically, has been regulated in Law Number 14 Year 2002 on Tax Court. However, there is an issue relating to the ambiguous position of the Tax Court. Purpose. The purpose of this is to show that the position of the court is not independent, as it plays a role in both judicial and executive functions, which may result in a lack of independence in case decision making. Therefore, this study aims to determine the position of the tax court in the current judicial system in Indonesia. Method. This research uses normative juridical research method by reviewing secondary data obtained. Based on the results of the research, it was found that the latest Constitutional Court Decision Number 26/PUU-XXI/2023 has determined that the Tax Courts must transfer their organizational, administrative, and financial development responsibilities to the Supreme Court before 31 December 2026. Results. The consequence of this decision is that the organizational structure of the Tax Court will be directly under the supervision of the Supreme Court and no longer under the Ministry of Finance. Although the Tax Court will be transferred to the Supreme Court, it is important to maintain this situation as the transition requires adjustments in terms of organizational structure, employee status, and career opportunities for tax judges. All of these matters must be studied and solutions found by the Tax Court as the independence of tax judges means a lot to taxpayers seeking justice in their tax disputes. Conclusion. In addition to independence, the public also expects competent expertise and knowledge from tax judges as enforcers of justice in tax disputes.